The interplay between anthropometric profile, surfboard dimensions, and surfboard design and selection processes in competitive female and male surfers - Gosney, S.; MacDonald, L.; Parsonage, J.; Worsey, M.; Denny, A.; Minahan, C. (International Journal of Sports Science & Coaching, 2025)
Surfboards are a critical component of surfing performance, yet the relationship between a surfer's anthropometric profile and their surfboard dimensions, as well as the factors influencing surfers` decision-making around surfboard design and selection within competition, remains unexplored. Forty-two competitive surfers participated in this study. Of the forty-two surfers, the anthropometric profile of twenty-eight females (n = 12) and males (n = 16) was determined (i.e., height, body mass, arm span, body composition), while thirty-one females (n = 15) and males (n = 16) completed a survey to determine their decision-making towards surfboard design and selection within competition. The results demonstrated fewer significant correlations between the anthropometric profiles and surfboard dimensions of female surfers than male surfers and the anthropometric profiles of female surfers explained less variance in their surfboard dimensions compared to male surfers. Fat mass measures contributed more to the variance in female surfers` surfboard dimensions, whereas lean mass measures contributed more to the variance for male surfers. Survey results also determined that female surfers rated the factors informing their decision-making around surfboard design and selection as less influential compared to male surfers. These findings highlight notable sex-related differences in the relationship between surfers` anthropometric profile and their competition surfboards, as well as their decision-making processes. Increased exposure and experimentation with surfboard design could benefit female surfers and advance their performance in the sport alongside their male counterparts.